Two new species of Impatiens (Balsaminaceae) from the Western Ghats, India - Mani, Bince; Thomas, Sinjumol; Britto, S. John (Phytotaxa, 2018)
Impatiens saulierea and I. josephia, two new species, are described from the Western Ghats, India. The former is collected from Kakkayam, Kozhikode and the latter from Idukki, Kerala. A detailed description of both taxa along with diagnostic characters between allied species, conservation status, pollen morphology and colour photographs are provided.